Burnout syndrome and weekly workload of on-call physicians: cross-sectional study - Barbosa, Fabiano Timbó (2012)
CONTEXT AND OBJECTIVES: Burnout syndrome (BS) is characterized by three dimensions: emotional exhaustion, depersonalization and reduced personal fulfillment. The objectives of this study were to evaluate a possible association between BS and weekly workload, and to describe the prevalence of BS and the sociodemographic and occupational profile of on-call physicians in Maceió. DESIGN AND SETTING: Cross-sectional study in intensive care units (ICU) at public and private hospitals in Maceió. METHODS: A self-administered form was used to evaluate sociodemographic characteristics and BS through the Maslach Burnout Inventory (MBI) among 67 on-call physicians at ICUs in Maceió. Pearson’s R correlation test was used to compare workload and emotional exhaustion. For other dimensions, Spearman’s S test was used (P < 0.05). Other variables were represented by simple frequencies. The 95% confidence interval was calculated for each variable. RESULTS: Among the physicians studied, 55.22% were female and the mean age was 43.9 ± 8.95 years. The mean weekly workload on call was 43.85 ± 24.49 hours. The frequency of high scores in at least one of the three dimensions of MBI was 70.14%. CONCLUSIONS: Despite the high prevalence of BS, especially among physicians who did not practice regular physical activity, our data did not indicate any significant correlation between weekly workload and any of the three dimensions of BS in this sample. The high prevalence of BS draws attention to the importance of investigating other possible causes, in order to prevent and adequately treat it.